Allocation of annual electricity consumption and power generation capacities across multiple voltage levels in a high spatial resolution - Hülk, Ludwig; Wienholt, Lukas; Cußmann, Ilka; Müller, Ulf Philipp; Matke, Carsten; Kötter, Editha (International Journal of Sustainable Energy Planning and Management, 2017)
The electrical energy system is in transition. There is continuing expansion of renewable generation, which causes a spatial and temporal shift of energy flows at different voltage levels of the power grid. On the consumption side, demand patterns are expected to change. The limited availability of data with high spatial resolution hinders independent and transparent assessments. In view of this, the research project open_eGo is developing methods focusing on electricity networks and open-science principles. In this work, electricity demand and power generation are allocated to their corresponding voltage levels and network nodes. By combining data on municipal boundaries with Voronoi cells we created catchment areas for each substation. On the demand side, OpenStreetMap data is used for mapping different demand sectors. We show that a consistent data set can be produced in a high spatial resolution using geographical data processing. Our results apply to Germany but the methodology can be adopted to other countries or regions where sufficient open data is available.